Investigating the Role of Women Architects in Contemporary Iranian Architecture (1320-1977) - Sanaz Khanbanzadeh; Maryam Armaghan; Jamaleddin Soheili (زن در فرهنگ و هنر, 2020)
Women professional activity in Iran before the Qajar era was not traditional, but by the middle of the Qajar period women were given the opportunity to participate in society. Since the presence of women architects in contemporary Iranian architecture is often overlooked, the purpose of this study is to introduce women architects in Pahlavi era and to study their influence in architectural fields. The main purpose of this research is to evaluate the architectural areas performed by women architects during Pahlavi era and argue their influences in tyhis field. It is assumed that women's work in the professional field has had a greater impact. For this purpose, the paper has a qualitative methodology with historical-interpretive research method. Data have been collected from oral history, documentation and library, and interviews with architecture pioneers. Hence, the performance of women architects is independent variable and the amount of activity and their achievements in the field of architecture are dependent variable. The results indicate that while studying at university and working in the offices of architecture and construction development in the country, there is a reason that works of women architects in the professional fields can have more achievements than their works in academic areas; but they are still influential in the academic field.